Curse for true love - Stephanie Garber (London Hodder and Stoughton, 2024)
Evangeline Fox ventured to the Magnificent North in search of her happy ending, and it seems as if she has it. She's married to a handsome prince and lives in a legendary castle. But Evangeline has no idea of the devastating price she's paid for this fairytale. She doesn't know what she has lost, and her husband is determined to make sure she never finds out . . . but first he must kill Jacks, the Prince of Hearts. Blood will be shed, hearts will be stolen, and true love will be put to the test in A Curse for True Love, the breathlessly anticipated conclusion to the Once Upon A Broken Heart trilogy.
Keywords: American Fiction